PERKAWINAN SEMARGA DALAM HUKUM ADAT MANDAILING (Studi di Desa Manegen Kecamatan Padangsidimpuan Tenggara Kota Padangsidimpuan) - Ardina Khoirunnisa; Rosnidar Sembiring; Idha Aprilyana; Yefrizawati Yefrizawati (USU LAW JOURNAL, 2018)
ABSTRACT Mandailing society using the system of kinship patrilineal people, who know and use the term clan groups. Clan name is in fact the forerunner of a group of relatives according to the lineage of the father. The implementation of customs and customary law in public life carried out based on the structure and Mandailing systems customary law called Dalihan Na Tolu. Mandailing society has a marriage exogami, therefore semarga under the terms of the marriage customs of the Mandailing is prohibited. The prohibition of marriage semarga is already washed out in the community due to the influx of Mandailing influence of Islamic law. Formulation of the problem in this research is how the provisions of the customs of the Mandailing about marriage semarga, how the implementation of semarga marriage in the village in Mandailing Manegen society, and whether the legal consequences over the violation of the prohibition of Mandailing society semarga marriage in the village of Manegen.This research is empirical juridical legal research with descriptive research analytical nature. Research location in the village of Padangsidimpuan Sub-district Manegen Southeast Padangsidimpuan Town with a population of 1,120 persons and a sample of 20 people doing marriage semarga. The data used the data of primary and secondary legal materials that consist of primary, secondary, and tertiary. Data collection tools and techniques performed with the study of librarianship and study the field by doing the interview. The data analysis done with the method of qualitative analysis. Keywords: Custom Mandailing, Marriage Semarga, Mandailing Society, and Clans.